Constitutionality of enforcement of claims by private enforcement agents - Bodiroga Nikola (Anali Pravnog Fakulteta u Beogradu)
The main focus of this paper is legal status of private enforcement agents in Serbia. The 2011 Serbian Law on Enforcement and Security has introduced private enforcement agents as legal professionals in charge mainly for carrying out of the enforcement. Special enforcement procedure for collection of utilities and similar claims has become exclusive competence of private enforcement agents. Since enforcement procedure has always been regarded as a set of coercive measures against enforcement debtor, it became questionable whether this coercion could be exercised by private enforcement agents. It has been argued by legal scholars that enforcement of civil judgments and other enforcement deeds belongs only to the state authority. The author tackles this issue from the standpoint of decisions of constitutional courts and jurisprudence of European Court of Human Rights.